KONSEP SAHABAT MENURUT MAá¸¤FÅªáº’ AL-TARMASÄª (1842-1920 M) - Muhammad Anshori (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2017)
This article tries to explore the concept of shahabat in a book Manhaj Å»awÄ«al-Naáº“ar written by Maá¸¥fÅ«áº“ al- TarmasÄ«. This book is Shará¸¥ Naáº“m AlfÄ«yah al-SuyÅ«á¹Ä« (died in 911 H) consisting of 980 stanzas, and is added 20 stanzas by al-TarmasÄ«, so the total is 1000 stanzas. One of the interesting point to be discussed in hadith study is the concept of shahabat, the first source of hadith. The validity of shahabat becomes polemic between Sunni and Shiâ€™i, especially on the concept of shahabat justice. In the book, there is no new concept of shahabatâ€™s justice in general. Al- TarmasÄ« only repeats the previous ulamaâ€™s explanations in his book. By following the majority of ulama, he states that all shahabat are Ädil (fair), but the reality shows that not all of them are Ädil (fair). This article has been proved it by quoting some sources. Modern Muslim scholars also ask about the concept of al-á¹£aá¸¥Äbah kulluhum udÅ«l. In some literatures, it has been mentioned some shahabatâ€™s attitudes that did not show the Islamic values. There are many examples of bad shahabatâ€™s behavior, so it can be said that the concept of al-á¹£aá¸¥Äbah kulluhum udÅ«l does not have to be understood that all shahabat are Ädil (fair). The appropriate meaning is that some of shahabat are Ädil (fair) since â€œkulluâ€ here is juzâ€™iyah (some), not kulliyah (whole). Keywords: Ädil, Maá¸¥fÅ«áº“ al-TarmasÄ«, Manhaj Å»awÄ«al-Naáº“ar, Sahabat